Infliximab pri zdravljenju hudega na kortikosteroide neodzivnega zagona ulceroznega kolitisa - prikaz primera - Urlep Žužej, Darja (Zdravniški vestnik, 2004)
Background. The natural course of ulcerative colitis (UC) can be complicated with an acute severe attack of high degree of activity of inflammation which represents a life-threatening condition. High-dose intravenous steroids have been the treatment of choice for induction of clinical remission of acute severe attack. In corticosteroid refractory ulcerative colitis a surgical therapy is required. Patients and methods. A case of a ten year-old girl with severe steroid-refractory UC is presented. The treatment with infliximab was introduced with intention to avoid colectomy. After the first infusion of infliximab her condition improved and clinical remission was achieved which was maintained with azathioprine. Conclusions. Therapy with infliximab can be successful for a severe steroid-refractory UC. The patients treated with infliximab can avoid surgical therapy (colectomy) which can represent a life-long disablement. The achieved remission is best maintained with conventional immunosuppressive therapy (azathioprine or 6-mercaptopurin).
Keywords: Child; Colitis, ulcerative; Otrok; Therapy; Ulcerozni kolitis; Zdravljenje